IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA TEMA GAYA HIDUP BERKELANJUTAN PADA DIMENSI GOTONG ROYONG KELAS IV SDN 2 NGARGOSARI - Adnan Yusuf Hakim; Husni Wakhyudin; M Yusuf Setya Wardhana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The context of the research that drives this research is that researchers want to know how the implementation of the Pancasila Student Profile Strengthening Project on the theme of sustainable lifestyle with the dimension of mutual cooperation in grade IV at SDN 2 Ngargosari, then what are the reasons for the school to choose the theme of sustainable lifestyle with the dimension of mutual cooperation and what are the obstacles experienced. The problem in this study is how to implement the project to strengthen the profile of Pancasila students with the theme of sustainable lifestyle in the dimension of mutual cooperation at SD Negeri 2 Ngargosari. The purpose to be achieved in this study is to describe the project of strengthening the profile of Pancasila students on the theme of sustainable lifestyle in the dimension of mutual cooperation at SD Negeri 2 Ngargosari. This type of research is qualitative research. The data obtained are analyzed and presented in a descriptive form. The source of data in this study was sourced from the Principal and grade IV teachers of SDN 2 Ngargosari. The process of collecting data in this study was by making observations, conducting interviews with the principal and also grade IV teachers, then by distributing questionnaire questionnaires to grade IV students. The results in this study show (1) there are still some students who are still lacking in showing an attitude of cooperation, especially with their group mates. (2) Some teachers who are still students are considered incompetent in teaching. (3) Some students still underestimate the importance of implementing a sustainable lifestyle in daily life. (4) the implementation of a sustainable lifestyle is considered boring for some students.